(untitled) (Research, Society and Development, 2022)
The work must be carried out in conditions of immediate safety and free from disease, in the medium and long term. The nurse is characterized by being a professional who is often prone to risks to their health and safety in their work environment. The study aimed to analyze the scientific evidence on the importance of the safety of Nursing workers in the work environment and describe the main occupational risks that nursing workers face in the prevention of accidents and in the care of diseases in the organizational environment. This is an integrative literature review, in which the search for studies took place in the Latin American and Caribbean Health Literature database (LILACS), in the Nursing Database (BDENF) accessed through the Virtual Health Library, as well as, in the Electronic Library of the Scientific Electronic Library Online (SciELO) between August and October 2021. Thus, primary, qualitative studies that addressed the subject in question were included. The results showed that the biggest barrier is the fact that the occupational health nursing professional is in a mediation plan between two categories that can be antagonistic, the company and the workers. In this way, it is concluded that the professional who works in the hospital environment is exposed to work accidents, mental and emotional exhaustion, work overload, insufficient number of professionals, inadequate physical conditions, incorrect use of PPE, affecting the worker’s professional performance and putting people involved in the care process at risk.